(untitled) (Huellas, 2015)
Pehuén Co is a fast-growing seaside resort located in the “Coronel de Marina Leonardo Rosales” district in the Province of Buenos Aires. This dynamic growth of the area is not only related to the inflows of tourists but also to the settlement of second residents. The second resident is a dweller that owns a house, which he/she generally visits on weekends or on holidays. This type of residential tourism is the product of an improved economic situation and renewed motivations such as the search for tranquility, a better quality of life and a “refuge” from urban stress, encouraged by an increase of leisure time activities. However, the absence of any official data in relation to the population sector in Pehuén Co does not allow for its analysis or explanation, heightening this absence and constituting an invisible sector, fact that is not being considered by the current administration either. The primary objective of the present work is to determine the dominant role of the second resident as a driving force in Pehuén Co, if we consider him/her a potential resident in the framework of the comprehensive process of generation of residential tourism. The specific objectives are to single out this unit of analysis- the second resident, to define its profile, to explain its relationship with housing and the geographical space it forms part of in order to determine adequate management schemes. The concept of “specific imaginaries” that guides the second resident’s actions is paramount in understanding the dialectic relationship between second residence and second opportunity. The second Pehuén Co resident has the possibility to choose where to grow older or where to spend the last stage of his life. This highlights the possibility to conclude a life project of utmost importance for its protagonist. However, for the time being, the town management is not free from faults and this unit of analysis goes unnoticed. This situation raises concerns if we consider that the seaside resort will be, due to its geographic characteristics, a key area of attraction in the long term. Therefore, the role of a participatory management that will consider the opinion of second residents is crucial.